2005
DOI: 10.1158/0008-5472.can-04-3087
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor in Non–Small Cell Lung Cancer—A Potent Prognostic Factor and Possible Target for Endocrine Therapy

Abstract: A possible involvement of gender-dependent factors has been postulated in development of human non-small-cell lung cancers (NSCLC), but its details remain unclear. In this study, we examined biological significance of progesterone receptor in NSCLCs. Progesterone receptor immunoreactivity was detected in 106 of 228 NSCLCs (46.5%). Progesterone receptorpositive NSCLC was frequently detected in female and adenocarcinoma, and was inversely associated with tumornode-metastasis stage and histologic differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
2
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 46 publications
8
139
2
10
Order By: Relevance
“…A great majority of breast carcinomas are positive for ERa and SERMs such as tamoxifen or aromatase inhibitors such as letrozole are being used clinically as antiendocrine therapies for ERa-positive breast carcinoma patients. In NSCLC, ERh immunoreactivity has been found to be frequently positive (6,14,27,28), whereas the status of ERa immunoreactivity showed marked variability in its frequency of immunopositivity (0-73%) among the different studies reported (5, 14, 27, 29 -31). In these previously reported investigations, the same ERa antibody employed in our present study (clone 6F11) was used in three groups, in which ERa positivity was 0% (30), 38% (14), and 66% (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A great majority of breast carcinomas are positive for ERa and SERMs such as tamoxifen or aromatase inhibitors such as letrozole are being used clinically as antiendocrine therapies for ERa-positive breast carcinoma patients. In NSCLC, ERh immunoreactivity has been found to be frequently positive (6,14,27,28), whereas the status of ERa immunoreactivity showed marked variability in its frequency of immunopositivity (0-73%) among the different studies reported (5, 14, 27, 29 -31). In these previously reported investigations, the same ERa antibody employed in our present study (clone 6F11) was used in three groups, in which ERa positivity was 0% (30), 38% (14), and 66% (29).…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, ERh immunoreactivity has been found to be frequently positive (6,14,27,28), whereas the status of ERa immunoreactivity showed marked variability in its frequency of immunopositivity (0-73%) among the different studies reported (5, 14, 27, 29 -31). In these previously reported investigations, the same ERa antibody employed in our present study (clone 6F11) was used in three groups, in which ERa positivity was 0% (30), 38% (14), and 66% (29). In addition, Dabbs et al (29) reported that nuclear ERa immunoreactivity was detected with the 6F11 clone but not with the 1D5 clone, and these authors suggested that variability in ERa immunoreactivity might be due to different epitope recognized by the antibodies used in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies (7,16), we showed that A549, provided by Cell Resource Center for Biomedical Research (Tohoku University, Sendai, Japan), did not have detectable levels of ERα and ERβ proteins and was unresponsive to estradiol treatment in reporter gene assay. A549 used in this study was the same stock as in the previous study (16). Estradiol and testosterone were obtained from Sigma-Aldrich.…”
Section: Lung Carcinoma Cell Lines and Culture Conditionsmentioning
confidence: 95%
“…It is believed that the physiological action of P4 is mediated through either nuclear PR or membrane-bound receptors. A549 cells were reported to be nPR positive in previous research (32). To exclude the possibility that nPR could mediate the effect of P4 in A549 cells, we applied a pre-incubation of MIF, a P4 antagonist.…”
Section: Molecular Pathways Involved In the P4+pp1-induced Cell Migramentioning
confidence: 99%